Menopause and diabetes: EMAS clinical guide. (November 2018) - Slopien, Radoslaw; Wender-Ozegowska, Ewa; Rogowicz-Frontczak, Anita; Meczekalski, Blazej; Zozulinska-Ziolkiewicz, Dorota; Jaremek, Jesse D.; Cano, Antonio; Chedraui, Peter; Goulis, Dimitrios G.; Lopes, Patrice; Mishra, Gita; Mueck, Alfred; et al.
Highlights: Menopause is associated with an adverse metabolic profile that increases the risk of diabetes. Menopausal hormone therapy has a favourable effect on glucose homeostasis both in women with and in women without diabetes. The presence of diabetes is not a contraindication to menopausal hormone therapy. An individualised approach is recommended. Lifestyle intervention, including diet and exercise, constitutes the cornerstone for diabetes prevention and management. The choice of antidiabetic medications should be based on their metabolic, cardiovascular and bone effects. Abstract: Introduction: Whether menopause increases the risk of type 2 diabetes mellitus (T2DM) independently of ageing has been a matter of debate. Controversy also exists about the benefits and risks of menopausal hormone therapy (MHT) in women with T2DM. Aims: To summarise the evidence on 1) the effect of menopause on metabolic parameters and the risk of T2DM, 2) the effect of T2DM on age at menopause, 3) the effect of MHT on the risk of T2DM, and 4) the management of postmenopausal women with T2DM. Materials and methods: Literature review and consensus of experts' opinions. Results and conclusion: Metabolic changes during the menopausal transition include an increase in and the central redistribution of adipose tissue, as well as a decrease in energy expenditure. In addition, there is impairment of insulin secretion and insulin sensitivity and an increase in the risk of T2DM. MHT has a favourable effect on glucose metabolism, both in women with and in women without T2DM, while it may delay the onset of T2DM. MHT in women with T2DM should be administered according to their risk of cardiovascular disease (CVD). In women with T2DM and low CVD risk, oral oestrogens may be preferred, while transdermal 17β-oestradiol is preferred for women with T2DM and coexistent CVD risk factors, such as obesity. In any case, a progestogen with neutral effects on glucose metabolism should be used, such as progesterone, dydrogesterone or transdermal norethisterone. Postmenopausal women with T2DM should be managed primarily with lifestyle intervention, including diet and exercise. Most of them will eventually require pharmacological therapy. The selection of antidiabetic medications should be based on the patient's specific characteristics and comorbidities, as well on the metabolic, cardiovascular and bone effects of the medications.